THE INFLUENCE OF USE OF POP-UP BOOK MEDIA ON THE MENTAL HEALTH OF SCHOOL-AGE CHILDREN AT THE FOUNDATION OF SUMATRA RINDANG - Nasution, Riska Amalya; Siska; Ekawaty, Fadliyana; Rts, Netisa Martawinarti; Rina Oktaria; Ilham Falani (Sekolah Tinggi Ilmu Kesehatan Garuda Putih, 2025)
Orphans are a special group of children who are generally marginalized and vulnerable to mental disorders. Efforts that can be made are to provide education about the importance of maintaining mental health as an effort to improve mental health. So that education can be easily understood by school age children, education needs to be delivered using varied media, namely pop-up book media because pop-up books provide surprises on every page which will make the story even more real. This research aims to determine the effect of using pop up book media on the mental health of school-aged children. This research is a quasi-experimental quantitative research using a pretest-posttest control group design approach with 20 respondents divided into 10 intervention groups and 10 control groups. Data measurement with the SDQ instrument. Univariate data analysis using frequency distribution. Bivariate analysis uses paired t-test. The results of mental health research after being given pop-up book media were that in the intervention group, 10 respondents were in the normal category (100%) while in the control group 8 respondents were in the abnormal category (80%) and 2 respondents were in the borderline category (20% . which was tested using the paired t-test, the p-value was 0.001 or p < 0.05. This shows that there is a significant difference in mental health before and after being given education using pop up book media. There is a significant influence between mental health before and after being given pop-up book media at the Sumatra Rindang Foundation. It is hoped that the Sumatra Rindang Foundation can develop pop-up book media for a more interesting and effective learning process.